2016
DOI: 10.1016/j.jsbmb.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of steroidogenesis: Cell models for mechanistic investigations and as screening tools

Abstract: In the modern world, humans are exposed during their whole life to a large number of synthetic chemicals. Some of these chemicals have the potential to disrupt endocrine functions and contribute to the development and/or progression of major diseases. Every year approximately 1000 novel chemicals, used in industrial production, agriculture, consumer products or as pharmaceuticals, are reaching the market, often with limited safety assessment regarding potential endocrine activities. Steroids are essential endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 203 publications
(222 reference statements)
0
28
0
Order By: Relevance
“…Studies on endocrine disruption of exogenous compounds, particularly regarding steroidogenesis, have focused mainly on gene expression and activity of steroidogenesis enzymes 24, 25 , especially aromatase 26, 27 , although multiple factors could be involved in steroidogenesis. In this research, we demonstrated that MCP pesticide acted on many target sites, affecting the transport of cholesterol and gene expression of steroidogenesis enzymes, leading to abnormal levels of sex hormone synthesis intermediates and effectual hormones, and thus resulting in a proportional imbalance of sex hormones in male goldfish.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on endocrine disruption of exogenous compounds, particularly regarding steroidogenesis, have focused mainly on gene expression and activity of steroidogenesis enzymes 24, 25 , especially aromatase 26, 27 , although multiple factors could be involved in steroidogenesis. In this research, we demonstrated that MCP pesticide acted on many target sites, affecting the transport of cholesterol and gene expression of steroidogenesis enzymes, leading to abnormal levels of sex hormone synthesis intermediates and effectual hormones, and thus resulting in a proportional imbalance of sex hormones in male goldfish.…”
Section: Discussionmentioning
confidence: 99%
“…This process is initiated by the transfer of a hydrophobic molecule of cholesterol from the outer to the inner membrane of the mitochondria, which enables StAR protein, a part of the StAR‐related lipid transfer domain family (Rathor et al, ). Cholesterol might be produced directly in cells from acetyl‐coenzyme A or come from dietary products (Odermatt, Strajhar, & Engeli, ). Then, cholesterol is converted to pregnenolone, a precursor of all steroids, by CYP cholesterol side chain cleavage enzyme (CYP11A1), finally to produce tissue‐specific hormones: androgens, estrogens, glucocorticoids as well as mineralocorticoids (Doghman‐Bouguerra & Lalli, ).…”
Section: Steroidogenesismentioning
confidence: 99%
“…Then, cholesterol is converted to pregnenolone, a precursor of all steroids, by CYP cholesterol side chain cleavage enzyme (CYP11A1), finally to produce tissue‐specific hormones: androgens, estrogens, glucocorticoids as well as mineralocorticoids (Doghman‐Bouguerra & Lalli, ). Steroids are produced in the adrenal glands, gonads (testis and ovaries) as well as in the placenta during pregnancy (Odermatt et al, ). Steroidogenesis is also present in other organs expressing steroidogenic enzymes such as the brain, intestinal tract and skin, although its action is mainly restricted to local tissue (Odermatt et al, ).…”
Section: Steroidogenesismentioning
confidence: 99%
See 2 more Smart Citations